A comparison of serve speed and motor coordination between elite and club level tennis players - Sögüt, M. (Journal of Human Kinetics, 2017)
The purpose of this study was to compare the serve speed and motor coordination of elite and club level junior tennis players aged 11-14 years. Participants (n=35) were assigned to one of the two groups according to their experience, weekly training volume and competition level. Serve speed was assessed with a sports radar gun. Motor coordination was evaluated by means of the Körperkoordinationstest für Kinder. The main results revealed that serve speed and motor coordination performance levels of the elite group were significantly higher than those of the club group. This study emphasized the importance of early participation and training intensity, which can play an important role in enhancement of serve speed and motor coordination.